Dampak Environmental, Social, Dan Governance (ESG) Terhadap Kinerja Keuangan - Wahdan Arum Inawati; Rahmawati Rahmawati (Universitas Muhammadiyah Malang, 2023)
Purpose: The objective of this study is to assess how social, environmental, and governance factors impact the financial performance of companies in non-financial sectors. These three factors are assessed based on the Global Reporting Initiative (GRI) standard indicators. In addition, financial performance as a dependent variable is proxied through the Return on Assets (ROA) ratio. Methodology/Approach: This study used quantitative data with a purposive sampling approach and selected 32 non-financial sector companies with a research period from 2019 – 2021, so that the number of research observation data used was 96 samples. Regression analysis of panel data is used for testing research hypotheses. Data analysis techniques start from descriptive statistical analysis, classical assumption tests, panel data regression model selection tests, determination coefficient tests (R2), simultaneous tests (f), and partial tests (t). The fixed effect model was selected for this study after the chow test and hausman test. Findings: The findings of this study show that social factors, environmental factors, and governance factors have a positive influence on the financial performance of non-financial sector companies. This research provides an understanding of the application of ESG and its impact on the financial performance of non-financial sector companies in 2019-2021. Practical and Theoretical Contribution/Originality: The implication is that increasing awareness and compliance with corporate social responsibility on the environment, social and governance on the impact of the company's operational activities is a way for corporate sustainability.